Tinjauan Filosofis Kepastian Hukum Bagi Pemerintah Daerah Dalam Implementasi Undang-Undang Penanaman Modal - Ramlan ' (Fakultas Hukum Universitas Riau, 2012)
State duty to promote the general welfare of its people.For that, one of the policies pursued by the Govern-ment is giving authority to local governments to imple-ment and execute development activities as well asgreater authority in obtaining sources of financing,by way of delegated authority on local governmentinvestments. Due to matters concerning local govern-ment in the field of investment only on the criteria ofexternality, accountability, and efficiency, what ismeant by these criteria are not clear in its elaboration.